(untitled) (Jurnal Psikologi Udayana, 2016)
Acute Lymphoblastic Leukemia is a type of blood cancer that holds a percentage of 65% of all childhood leukemia incidence (Muhtadi, 2014). Symptoms of the disease and the therapeutic effects of treatment that must be taken in a minimum period of two years, requires children to fight for his recovery (Pre-eliminary interview study). Often the circumstances experienced by children with acute lymphoblastic leukemia during therapy treatment is contrary to the child’s personality. Thus, children need to make an effort to overcome the unpleasant condition during therapy treatment. The effort is called the coping strategies (Spencer, Jeffrey, & Greene, 2002). Gamayanti (2006) revealed that children who have good coping would improve the continuity of the therapy process and to give effect to the development of children after recovery. According to this fact, the researcher want to determine how the coping strategies in children with acute lymphoblastic leukemia during therapy treatment. This study is qualitative research with case study design. Interview, observation, and documentation are used to collecting data, of two children with acute lymphoblastic leukemia. In order to strengthen the data, interview techniques focused on two significant others of children with acute lymphoblastic leukemia. The results in this study shows that children with acute lymphoblastic leukemia has a coping strategy. A complete overview coping strategies will be discussed in accordance with the circumstances of the child during therapy treatment. Keywords: Coping strategies, children with acute lymphoblastic leukemia